PAM-1: an antimicrobial peptide with promise against ceftazidime-avibactam resistant Escherichia coli infection - Han, Yijia; Zhang, Yi; Zhang, Xiaodong; Huang, Zeyu; Kong, Jingchun; Wang, Xiuxiu; Chen, Lijiang; Wang, Yue; Cao, Jianming; Zhou, Tieli; Shen, Mo (Frontiers in Microbiology, 2024)
Antibiotic misuse and overuse have led to the emergence of carbapenem-resistant bacteria. The spread of ceftazidime-avibactam (CZA), a new antibiotic combination, resistance is becoming a severe problem for people worldwide. In the present study, we elucidated the antibacterial action and potential mechanism of PAM-1, an antimicrobial peptide derived from the platypus, against CZAresistant Escherichia. Coli (E. coli). Furthermore, we evaluated the stability and safety of PAM-1 in diverse environments and determined its anti-inflammatory effect. In vitro antibacterial experiments demonstrated that the MICs of PAM-1 ranged from 2 to 8 μg/mL, with its effectiveness sustained for a duration of 24 h. PAM-1 exhibited significant antibiofilm activities against CZA-resistant E. coli (p < 0.5). Furthermore, propidium iodide staining and N-phenyl-1-naphthylamine uptake experiments revealed that PAM-1 may exert its antibacterial effect by disrupting membrane integrity by forming transmembrane pores (p < 0.5). Red blood cell hemolysis and cytotoxicity tests to evaluate the safety of PAM-1 revealed that it exerts no adverse effects at experimental concentrations (p > 0.5).Moreover, stability tests revealed its effectiveness in serum and at room temperature. The Galleria mellonella infection model revealed that PAM-1 can significantly improve the survival rate of Galleria mellonella (>50%)for in vivo treatment. Lastly, RT-qPCR revealed that PAM-1 downregulates the expression of inflammatory cytokines (p < 0.5). Overall, our study findings highlight the potential of PAM-1 as a therapeutic agent for CZA-resistant E. coli infections, offering new avenues for research and alternative antimicrobial therapy strategies.2015 FDA(Food and Drug Administration) approval of ceftazidime-avibactam (CZA), a novel combination of a cephalosporin and a β-lactamase inhibitor. This innovative combination exhibits in vitro activity against Enterobacterales harboring β-lactamases of Ambler class A (including extended-spectrum β-lactamases [ESBLs] and Klebsiella pneumoniae carbapenemases [KPC]), class C (AmpC cephalosporinases), and some class D enzymes (e.g., OXA-48-type, many of which also possess ESBLs) (